Characterization of diatomite by X-Ray diffraction (2007)
An X-Ray diffraction technique to was used to a detail detail characterization of the clay minerals in a diatomite deposit, which has not been studied nor explored, in order to determine its mining and industrial potential, located in the Tunja_Chivatá (Boyacá) pilot area.